Nexus between Public Revenue, Public Expenditure and Economic Growth: Evidence from Nepal - Gyan Mani Adhikari; Rajendra Adhikari; Santosh Chhetri; Achyut Gyawali (ABM: International Journal of Administration, Business and Management, 2025)
The relationship between public revenue, public expenditure, and economic growth has been a subject of extensive debate in economic literature. This study investigates the dynamics between public revenue, public expenditure, and economic growth in Nepal over the period from 1975 to 2022, utilizing co-integration and Granger causality tests. The results of the analysis reveal a unidirectional causal relationship from nominal GDP to government revenue, suggesting that nominal GDP is a significant determinant of government revenue in the short run. The study underscores the importance of economic growth in forecasting public revenue, providing valuable insights into fiscal policy formulation and economic planning in Nepal.